Investor Sentiment Measurement of Merger and Acquisition Companies in Indonesia - Rizal, N. A. (Information Management and Business Review, 2013)
This research is conducted about how to measure the investor sentiment, when the prospects of merger or acquisition have completed. The measurement is done by examining the likelihood of success or failure, which can determine the investment strategy, while holding a target when it is still occurred. It is to see whether the positive investor sentiment should increase or decrease when the probability of the acquisition’s success increases or decreases and that sentiment will also vary with events during the period of offering. The purpose of this paper is to make a probability model that will describe about the investor sentiment behavior during the merger and acquisition process in Indonesia. This model will also separate the effect of Indonesia markets and target company’s movement. The samples are taken from the companies that listed in Jakarta Stock Exchange from 2009 and 2012. The information that we used in this research is the public news from the Regulator Committee of Business Providers (Komite Penyelenggara Pengawasan Usaha/KPPU) and the available newspaper in Indonesia. The result shows that after the first announcement, the investor sentiment react very enthusiasm and the trend line of the sentiment tend to increase against the stock price and the market.